The morpho-mechanical basis of ammonite form. - Moulton, D; Goriely, A; Chirat, R (2015)
Ammonites are a group of extinct cephalopods that garner tremendous interest over a range of scientific fields and have been a paradigm for biochronology, palaeobiology, and evolutionary theories. Their defining feature is the spiral geometry and ribbing pattern through which palaeontologists infer phylogenetic relationships and evolutionary trends. Here, we develop a morpho-mechanical model for ammonite morphogenesis. While a wealth of observations have been compiled on ammonite form, and several functional interpretations may be found, this study presents the first quantitative model to explain rib formation. Our approach, based on fundamental principles of growth and mechanics, gives a natural explanation for the morphogenesis and diversity of ribs, uncovers intrinsic laws linking ribbing and shell geometry, and provides new opportunities to interpret ammonites' and other mollusks' evolution.